Jenis Kemasan dan Lama Penyimpanan terhadap Karakteristik Sambal â€œMarotoâ€ Khas Sumba Barat Daya - Roseline Adiyaksa Maghu; I Putu Candra; I Gede Pasek Mangku (GEMA AGRO, 2019)
Southwest Sumba is one of the regencies in East Nusa Tenggara which has a special sambal which is very popular because of its interesting taste and aroma, the "maroto" sauce. This Sambal consists of simple ingredients namely cayenne pepper, garlic, kaffir lime, sugar and salt. How to process it is also very easy that all ingredients are pulverized and not given any additional preservatives but can be durable in a few days or even weeks. This study aims to determine whether bioplastic packaging is as effective as polypropylene plastic packaging (PP) in maintaining the characteristics of "maroto" chillies and how long the shelf life of "maroto" chillies at room temperature. The design used is a Completely Randomized Design (CRD) with two factors and two replications, the first factor is the type of packaging consisting of two types, namely polypropylene plastic packaging (PP) and bioplastic packaging. The second factor is the storage time which consists of four levels, namely first week, second week, third week and fourth week. Objective observations included: water content, total acid content, pH, vitamin C content and mold test and subjectively included: color, flavor and overall acceptance. The results obtained by bioplastic packaging have the same effectiveness as polypropylene plastic packaging (PP) in maintaining the characteristics of the "maroto" chilli on the parameters of water content, pH, total acid levels, vitamin C levels, test fungi, color, aroma, taste and overall acceptance. The storage time for "maroto" sauce in bioplastic packaging is three weeks and the storage time for "maroto" sauce in polypropylene (PP) plastic packaging is four weeks at room temperature of 28 Â± 1ÂºC.